The Effect of Potassium Fertilizer and Eco-Enzyme on the Growth and Production of Shallots (Allium ascalonicum L.) - Saragih, Meylin Kristina; Simanjuntak, Pantas; Panataria, Lince Romauli; Sitorus, Efbertias (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aimed to determine the effect of potassium fertilizer and eco enzyme on the growth and production of Shallots (Allium et al.). The study used a Factorial Randomized Block Design (RAK) with two factors studied. The first factor was KCL fertilizer (K) with four levels, namely: K0 = No Application, K1 = 10 grams/plot (equivalent to 100 kg/ha), K2 = 15 grams/plot (equivalent to 150 kg/ha), K3 = 20 grams/plot (equivalent to 200 kg/ha), The second factor Eco Enzyme (P) 3 levels, namely: P1 = 7 ml/liter of water, P2 = 10 ml/liter of waterP3 = 13 ml/liter of water. The results showed that potassium treatment significantly affected plant height 5 MST but had no significant impact at the ages of 2, 3, and 4 MST and the number of bulbs per sample. Eco-enzyme treatment had no significant effect on plant height or number of bulbs per sample. The interaction between potassium fertilizer and eco-enzyme had no significant effect on plant height and number of tubers per sample.